CONVERGENCE HYPOTHESIS AND ECONOMIC GROWTH: EVIDENCE FROMORGANIZATION OF ISLAMIC COOPERATION (OIC)COUNTRIES - Muhammad Ramzan Sheikh, Sanie Zahra, Muhammad Irfan Chani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This paper aims to investigate the convergence hypothesis and economic growth in a panalof selectedOICcountries over the period of time 1960-2018.Two measures have been used i.ebeta and sigma convergence.Results of calculations of beta and sigma convergence through regression analysis clearly reveals that beta convergence is positive among OIC countries.Findings confirm that overall income gap has widened in OIC nations in first three decades thus showing poor annual growth performance however income gap narrowed down in last subsequent decades exhibiting good growth performance.Lastly,pooled OLS regression analysis for Conditional Convergence under Solow Swanframework by using initial value method has been performed. Furthermore, in the context of policy implications, important policies are recommended to enhance GDP growth rate inthese countries. Policymakers may adopt such strategies which enhance the life expectancy,enrollment rate i.e.variables related to human capital formation and physical capital so that GDP growth of the selected economies may be accelerated.